Menyoal Framework Agama: Upaya Rekonsiliasi HAM Berat 1965 - Indra Doris, Yulius Edward (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The author's focus in this article is to question the religious framework in viewing the 1965 gross human rights case as one of the reconciliation efforts. Reconciliation of 1965 Gross Human Rights is an important effort to build peace and unity in Indonesia, especially in facing the political year. It is also important for the creation of peaceful politics. However, this effort faces challenges, one of which is the religious framework in viewing the 1965 Gross Human Rights case. The method used in this analysis is a historical study of the 1965 gross human rights violations case, especially regarding the role and involvement of religions in responding to this case. This article offers a religious framework that is more inclusive and emphasizes the characteristics of a religion of peace and love. This framework is based on the principles of humanity, justice and equality. The findings of this research are a new framework of religion that is broader and more open in viewing the 1965 Gross Human Rights Case that emphasizes love. This new framework is the basis for reconciliation for the Indonesian people. It is hoped that from this new framework, all elements of the nation can accept it so that the 1965 Gross Human Rights case has the same perspective in terms of religion. This is expected to bring political stability in Indonesia and free the Indonesian people from the 1965 Serious Human Rights issue.